2011
DOI: 10.1242/jeb.055582
|View full text |Cite
|
Sign up to set email alerts
|

Sheep rumen and omasum primary cultures and source epithelia: barrier function aligns with expression of tight junction proteins

Abstract: SUMMARYThe forestomachs of cows and sheep have historically served as important models for the study of epithelial transport. Thus, the ruminal epithelium was among the first tissues in which absorption of chloride against an electrochemical gradient was observed, requiring a tight paracellular barrier to prevent back-leakage. However, little is known about ruminal barrier function, despite the considerable implications for ruminant health. The tight junction proteins of the omasum have never been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 41 publications
8
56
0
Order By: Relevance
“…The primary antibodies employed were rb-anti-claudin-1, m-anti-claudin-4, manti-occludin, and rb-anti-ZO-1 (Invitrogen, dilutions of 1:500 for claudin-1 and ZO-1, 1:800 for claudin-4 and occludin). The specificity of the antibodies was previously verified by Stumpff et al (38) and was also confirmed in our preliminary experiment. After several washes with TBST, membranes were incubated in a 1:20,000 dilution of an anti-rabbit or anti-mouse HRP-conjugated secondary antibody (Sunshine Biotechnology, Nanjing, China).…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…The primary antibodies employed were rb-anti-claudin-1, m-anti-claudin-4, manti-occludin, and rb-anti-ZO-1 (Invitrogen, dilutions of 1:500 for claudin-1 and ZO-1, 1:800 for claudin-4 and occludin). The specificity of the antibodies was previously verified by Stumpff et al (38) and was also confirmed in our preliminary experiment. After several washes with TBST, membranes were incubated in a 1:20,000 dilution of an anti-rabbit or anti-mouse HRP-conjugated secondary antibody (Sunshine Biotechnology, Nanjing, China).…”
Section: Methodssupporting
confidence: 88%
“…In addition, the prominent histological alterations during HG feeding strongly suggest an impaired barrier function (35-37) that may provide the opportunity for the translocation of toxins and bacteria from the rumen into the blood, ultimately affecting animal health and productivity (28). Although there is fundamental knowledge about the consequences of HG feeding on ruminal epithelial barrier function, remarkably little information is currently available about the underlying molecular changes in ruminal epithelial barrier function during HG diet feeding.The rumen epithelium (RE) of sheep and cattle has extensive barrier-forming properties, depending on the multicellular structure (stratum corneum, granulosum, spinosum, and basale) and the junctional complex that establish a barrier between sometimes hostile external environments and the internal milieu (12,27,38). Tight junctions (TJs) located in the middle layers (stratum granulosum and spinosum) play a key role in maintaining the polarity of epithelial cells, regulating the permeability of the epithelial barrier and preventing the translocation of LPS and other toxins (12,27).…”
mentioning
confidence: 99%
See 3 more Smart Citations